Family Issues related to the Corona Pandemic - Shleibak أحمد الصويعي (Dirasat: Shari’a and Law Sciences, 2022)
Objectives: The research seeks to achieve several objectives, including: to demonstrate the relationship of the Corona epidemic to some family-related doctrinal issues and and to show the effects of the Corona epidemic on family calamities. Methods: The research used the inductive approach by tracking, collecting, and analysing data. It also used an extrapolating approach by inferring the legal provisions relating to the impact of the Corona epidemic on family-related issues, and the comparative approach by comparing the opinions of jurists about the issue. Results: The researcher reached a set of results, the most important of which are: Sharia has found solutions to jurisprudential issues that may occur due to corona disease, such as the wife if she contracted corona disease before moving to her husband’s house, then the husband must pay alimony. And if the bequeathed to him, if the corona disease was transmitted to the testator with the intent of killing him with the aim of rushing the will, and the testator died because of corona that the testator transmitted to him, the will will be invalidated, pursuant to “the opposite of his intention” principle. Conclusions: The research concluded that issues related to Corona disease should be studied, researched and resolved.